Redox-sensitive system of the antioxidant-responsive element as a new target for tuberculosis treatment - P. M. Kozhin; N. K. Zenkov; A. V. Chechushkov; N. S. Zaytseva; N. V. Kandalintseva; E. B. Menshchikova (Acta Biomedica Scientifica)
The emergence of drug-resistant TB caused by resistance to antibiotic strains of bacteria, prompted to search for new "organism-oriented" ("host-targeted") adjuvant treatment strategies. Free radical oxidation plays an important role in the development and exacerbation of the pathological process. The main system of cell protection from oxidative stress is the redox-sensitive signaling system of the antioxidant-responsive element of the Keap1/Nrf2/ARE, which includes the transcription factor Nrf2, which is under constant control of a repressor protein Keapl. Nrf2 regulates the expression of genes containing the antioxidant-responsive element ARE in their promoters, Keapl is a kind of molecular "sensor" of modifications in the intracellular homeostasis. The inextricable link between these molecular structures allows combining them into a single redox-sensitive signaling system Keap1/Nrf2/ARE. Nrf2 modulates resistance of the organism to various infections: activation of Nrf2 prevents the penetration and replication of influenza A virus, contributes to resistance to various bacterial agents (Salmonella typhimurium, Pseudomonas aeruginosa). The aim of this work was to study the influence of induction system Keap1/Nrf2/ARE on the formation of mycobacterial granulomas in vitro. In vitro model was used to study effect of induction of the redox-sensitive signaling system Keap1/Nrf2/ARE in time course of granuloma formation. It was found that the activation of Keap1/Nrf2/ARE system led to acceleration of granuloma formation, which was then replaced by the dissociation process. These data allowed us to consider Keapl/Nrß/ARE system as a new therapeutic target in the tuberculosis treatment.